Nrima ing pandum: Menerima atau pasrah dengan keadaan? - Mahanani, Safira; Herdiyanto, Yohanes Kartika (Jurnal Psikologi Ulayat, 2026)
Nrima ing pandum is a Javanese life philosophy that emphasizes acceptance of life reality. Although this concept has been widely discussed in cultural and local psychological studies, existing literature remains fragmented and often ambiguously interprets nrima ing pandum as passive resignation rather than an adaptive coping strategy. This scoping review aims to examine the meaning of nrima ing pandum and its psychological function as a coping strategy in dealing with life stress. The study employs a scoping review method to systematically collect and synthesize findings from relevant literature. A synthesis of 11 selected studies shows that nrima ing pandum contributes to emotional calmness, self-acceptance, resilience, and meaning-making across various stress contexts, including poverty, illness, aging, disasters, and emotional distress. However, several studies also reveal the risk of maladaptive outcomes when nrima is misunderstood as fatalistic surrender. These findings highlight the importance of a contextual and accurate understanding of nrima ing pandum as an active, culturally grounded coping strategy that can inform culturally sensitive mental health practices.